2016
DOI: 10.4236/ojn.2016.63016
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Gap in Saudi Nurses’ Knowledge of Dementia, Depression and Delirium (the 3Ds), and Investigating Their Relevant Experience: An Exploratory Study

Abstract: Aim: This study aims at testing registered nurses' knowledge while working at mental health facilities and general care hospitals, through an exploratory non-experimental study using a random sample of nurse population across Saudi health facilities. Materials and Methods: The study participants were asked to complete a questionnaire consisting of four sections. Section 1 consisted of 21 questions, requesting participants to provide their background and demographic information, followed by a delirium-knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Numerous studies aimed to investigate health professionals’ knowledge and perceptions regarding geriatric peoples and some neurological problems, such as dementia, where several reviews reported a lack of personnel trained in dementia care (Alaama, 2016; Alsenany & Alsaif, 2014; Halabi & Zafar, 2010; Yaghmour et al, 2016). In the KSA, a study found a knowledge deficit among medical students, despite geriatric medicine being introduced into a residency programme in early 2016 (Alaama, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies aimed to investigate health professionals’ knowledge and perceptions regarding geriatric peoples and some neurological problems, such as dementia, where several reviews reported a lack of personnel trained in dementia care (Alaama, 2016; Alsenany & Alsaif, 2014; Halabi & Zafar, 2010; Yaghmour et al, 2016). In the KSA, a study found a knowledge deficit among medical students, despite geriatric medicine being introduced into a residency programme in early 2016 (Alaama, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The results of focus groups and nursing faculty member surveys suggested that more gerontological content and clinical experiences are needed in the nursing curriculum (Alsenany & Alsaif, 2014). Another study investigated that nurses’ knowledge of dementia, depression and delirium found the need for increased dementia training, as insufficient dementia knowledge was detected among the study’s participants (Yaghmour et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations